Evaluating the potential impact of interruptions to neglected tropical disease programmes due to COVID-19 - Hollingsworth, TD; Mwinzi, P; Vasconcelos, A; de Vlas, SJ (Oxford University Press, 2021)
At the time of writing (February 2021), it is 1 y since the coronavirus disease 2019 (COVID-19) pandemic began to become a pandemic. To date, there have been >100 million cases of COVID-19 diagnosed globally, leading to at least 2.2 million deaths. The indirect effects of the pandemic on other health conditions, as well as economic and societal well-being, are accruing at an alarming rate. Probably due to its young population, perhaps combined with recent experience of combating large-scale epidemics, such as Ebola in 2014 and 2016, sub-Saharan Africa has been affected relatively modestly by COVID-19, with a death toll of about 60 000 cases so far, mainly in South Africa. However, these reported numbers may be underestimates, given the limitations of the local health systems. Also, the future course of the pandemic is highly uncertain, especially where large-scale vaccination campaigns may be more challenging than in high-income countries. Model predictions suggest that suspension of control efforts for malaria, TB and HIV in low- and middle-income countries could lead to deaths on a similar scale to those from COVID-19 itself. Similar effects were seen during the Ebola outbreak in West Africa, where the number of excess deaths due to other factors (including maternal mortality and particularly malaria) was estimated to be of the same order of magnitude as the number of deaths directly due to Ebola.